The end magnets of the IFUSP race-track microtron booster - Kassab, LRP; Gouffon, P.; Martins, M. N.; Takahashi, J. (Gordon Breach Sci Publ Ltd, 1998)
The end magnets of the IFUSP race-track microtron booster, second stage of the electron accelerator under construction at the Linear Accelerator Laboratory, are presented. They deflect, focus and return the beam to the accelerating section. Details about the project are discussed, Poisson code was used to give the final geometry of the end magnets. The end magnets incorporate auxiliary pole pieces (clamps) which create a reverse fringe field region that avoids the beam vertical defocusing and reduces the horizontal displacement produced by extended fringe fields (EFF). The small gap height used for the clamps provided reverse field distributions with fringe fields of short extensions, avoiding the traditional use of inactive clamps. Measurements and calculations concerning particle trajectories and reverse field distribution are presented. The floating wire technique, employing an original procedure to register orbits, was used to corroborate the calculated beam trajectories and represents a good experimental option in the lack of the accelerator beam. The experimental results showed agreement of about 0.1% with the calculations.
Keywords: IFUSP race-track; magnets; microtrons; floating wire; reverse fringe field